Perceptions of Policing and Security Among Hong Kong Migrant Sex Workers—a Research Note - Adorjan, Michael (Asian journal of criminology, 2019)
In this research note, I report findings from a small study examining Hong Kong sexworkers’perceptions of policing and security in Hong Kong. The major objective of this explorative project is to gauge perceptions of sex workers in Hong Kong that were chiefly recent migrants, meaning they were not native or born in Hong Kong. Specifically, it seeks to examine the attitudes and experiences of sex workers regarding policing in HongKong, specifically the Hong Kong Police Force and Immigration Department, both of whom are relevant given the varying degrees of legal status Hong Kong sex workers have while residing in Hong Kong.